PERBEDAAN TEKANAN DARAH SEBELUM DAN SETELAH TERAPI HUMOR DI KELURAHAN MERSI PURWOKERTO - Dwi Novitasari; Sidik Awaludin (Viva Medika, 2016)
Uncontrolled hypertension can lead to heart disease, kidney failure and stroke.Various complementary therapies developed to reduce high blood pressure. Joketherapy can cause a relaxation response and lowers blood pressure. The purpose ofthis study was to identify the impact of joke therapy on blood pressure.This study used the research design of One Group Pretest-Posttest Design. Theamount of samples of this study were 20 patients with hypertension in Mersi. Thesampling technique used purposive sampling.The results of the study showed a significant differences of the blood pressure beforeand after joke therapy humor therapy (p value sistolic = 0,000 dan p value = 0,004) Keyword: joke therapy, blood pressure, hypertension